The effects of environmental factors on the corrosion rate of TGIC-free polyester coated mild steel - Choo, Ling Qian (2010)
Nowadays, the applications of TGIC-free coated carbon steel in building industry is on the rise, mainly because it is less costly, effective in corrosion prevention and create least environmental hazards. However, the number of literatures focused on the technical evaluation of TGIC-free polyester coating as a corrosion protective layer is still very limited. The development in this green powder coating system mainly has focused on cost and health, environment and safety issues rather than new product development and product performance evaluation. The main purpose of this project is to investigate and compare the effects of solutions of different pH, seawater and tap water on the corrosion rates of TGIC-free polyester coated carbon steel and uncoated carbon steel of the same composition and dimension. The effects of these parameters on tensile strength and the significant or limitation of TGIC-free polyester coating also been investigated. The corrosion rate was determined by using weight loss method after a series of immersion tests and all these tests are done in accordance to ASTM G3 1. After the immersion test, both the coated and uncoated specimens were subjected to tensile test in accordance to ASTM E-8M. The laboratory result shows that this green coating system is effective in reducing the corrosion rates and increasing the tensile strengths of carbon steel under exposure to solutions of pH ranges from 3 to 12, tap water, and seawater. Also, TGIC-Free Polyester Coating shows particularly high durability in acidic solutions (solutions of pH 4 and below) and tap water.